Pengaruh Talent Acquisition Dan Employee Engagement terhadap Talent Retentions di UMKM - Alden Nelson; Delfina Muthia Sabella; Jessica; Nabila Arinov Mey; Rince Monica Hutagalung; Senly (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
In the era of modernization, the biggest challenge for business practitioners is how companies can keep up with developments and be effective in improving every aspect of their organization. Therefore, companies need to engage in talent retention to retain their best employees. The purpose of this article is to determine the influence of talent acquisition and employee engagement on talent retention in Small and Medium Enterprises (UMKM). This research employs a qualitative approach to gather in-depth and detailed information about the necessary theories. The method used in this analysis involves a literature review, commonly referred to as a literature study. The results of this analysis indicate the influence of talent acquisition and employee engagement on talent retention. Researchers recommend that UMKM engage in employee engagement to retain their best employees.